Prevalence of visual disturbances among medical undergraduate students of a tertiary care teaching hospital in South Kerala - V. S., Aparna; John, Kevin A.; Anvar , Rithima (International Journal Of Community Medicine And Public Health, 2023)
Background: Uncorrected errors of refraction are the leading cause of moderate to severe visual impairment. This study helps to determine the risk factors and prevalence of refractive error among medical students and to evaluate the uncorrected visual acuity among them. Aim was to study the prevalence and risk factors of visual disturbances among medical undergraduate students. Methods: A cross sectional study was conducted among 200 undergraduate medical students. Data on socio-demographic characteristics, type of refractive errors, risk factors for refractive errors and frequency of eye examinations were collected through questionnaires. Uncorrected visual acuity was detected using Snellens chart and near vision was tested using jaeger’s chart. Appropriate statistical tests were applied and data was analysed using statistical package for the social sciences (SPSS) version 21. Results: Out of the total 200 study participants, majority were females (61.5%), mean age of the study participants was 21.51±1.33, 11.5% were examined for the first time through this study, 51% were suffering from some sort of visual disturbance among which 80% were having myopia, 50% of the study participants spent more than two hours per day reading books, 72.5% had habit of reading in dim light. Uncorrected visual acuity was seen among 22% of the study subjects and 15% with positive family history of refractive errors showed uncorrected visual acuity. Conclusions: This study was an effort to identify the risk factors and determine the prevalence of refractive errors, 22% of subjects had uncorrected visual acuity; myopia was the common refractive error observed among the study participants followed by hypermetropia and astigmatism.